PENGARUH KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA PT. DINAMIK SENTOSA DI JAKARTA - Nurhadi, Ahmad (JGK (Jurnal Guru Kita), 2020)
Abstract: The Effect of Product Quality on Purchasing Decisions at PT. Dinamik Sentosa in Jakarta. This study aims to determine the effect of product quality on purchasing decisions at PT. Dinamik Sentosa in Jakarta. The method used is explanatory research with a sample of 87 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable product quality obtained an average score of 3.43 with good criteria. The purchase decision variable obtained an average score of 3.80 with good criteria. Product quality has a positive and significant effect on purchasing decisions with a regression equation value of Y = 8.879 + 0.850X, and a correlation coefficient value of 0.775 or has a strong level of relationship with a determination value of 60.0%. Hypothesis testing obtained a significance of 0.000